Body and mind in Zulu medicine : an ethnography of health and disease in Nyuswa-Zulu thought and practice - Ngubane, Harriet (Academic Press, 1977)
A Zulu woman anthropologist considers the role of women, who are the principal healers in Zululand and are believed to mediate between life and death. In a color symbolism valid all over sub-Saharan Africa, red mediates between white and black; red medicines bring the sick back from death into life.
free
Keywords: Zulu (African people) – Medicine